Le logement social au Nunavik - Aude Therrien; Gérard Duhaime (Recherches amérindiennes au Québec, 2018)
This article studies the participation of the regional stakeholders in the development and implementation of the Agreement respecting the implementation of the James Bay and Northern Québec Agreement on housing in Nunavik. This agreement is central, from a political point of view, to understand the housing situation in Nunavik since it determines the role of each stakeholder and establishes the level of funding provided for the construction of social housing. The agreement, first signed in 2000, was renewed in 2005 and 2010. If it had the initial goal to meet the Nunavik housing needs, the implementation, in 2011, of a dispute resolution mechanism and the absence of an agreement for its renewal in 2015 are signs that this agreement did not meet the desired goals of all the stakeholders. With a historical analysis of the agreement, the authors wish to highlight the powers of the different regional stakeholders and the differences that divide them. Cet article étudie la participation des acteurs régionaux à l’élaboration et à la mise en oeuvre de l’Entente concernant la mise en oeuvre de la Convention de la Baie-James et du Nord québécois en matière de logement au Nunavik. Cette entente est centrale, d’un point de vue politique, pour comprendre la situation du logement au Nunavik, puisqu’elle fixe les rôles de chacun des acteurs et établit le financement accordé pour la construction des logements sociaux. L’entente signée en 2000 a été renouvelée par deux fois, soit en 2005 et en 2010. Si elle avait pour but, lors de sa signature, de répondre aux besoins du Nunavik en logements, la mise en place en 2011 d’un mécanisme de résolution des différends et l’absence d’accord pour le renouvellement de l’entente quinquennale en 2015 sont des signes qu’elle ne rencontre pas les objectifs souhaités par l’ensemble des signataires. En ce sens, par une analyse historique de l’entente, les auteurs souhaitent mettre en lumière les pouvoirs que les différents acteurs régionaux exercent à travers cette politique et les différends ...